A hybrid friction-induced vibration form: Experimental measurement and mechanism discussion. (May 2023) - Wang, Quan; Wang, Zhiwei; Mo, Jiliang
Abstract: Friction-induced vibration (FIV) has strong nonlinear properties and complicated mechanism. In this research, the friction characteristics of a block-on-disc system with the variation of the speed are experimentally investigated. At a relatively medium speed, a hybrid vibration form composed of low-frequency stick–slip and high-frequency intermittent unstable vibration is discovered and denoted as stick–unstable sliding. Further, a mathematical model integrating the negative friction–velocity slope (NFVS) and mode-coupling theories is established to analyze the FIV and noise mechanisms at different speed levels. The results show that the FIV at relatively low and high speeds is respectively affected by the NFVS and mode-coupling. At a relatively medium speed, the NFVS and mode-coupling co-exist and then generate the stick–unstable sliding.